2021
DOI: 10.1155/2021/5573010
|View full text |Cite|
|
Sign up to set email alerts
|

Artificial Intelligence-Guided Subspace Clustering Algorithm for Glioma Images

Abstract: In order to improve the accuracy of glioma segmentation, a multimodal MRI glioma segmentation algorithm based on superpixels is proposed. Aiming at the current unsupervised feature extraction methods in MRI brain tumor segmentation that cannot adapt to the differences in brain tumor images, an MRI brain tumor segmentation method based on multimodal 3D convolutional neural networks (CNNs) feature extraction is proposed. First, the multimodal MRI is oversegmented into a series of superpixels that are uniform, co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 20 publications
(28 reference statements)
0
3
0
Order By: Relevance
“…Zhao uses bitter data processing and separation techniques to analyze the visual characteristics of a martial arts match. He evaluated abstract models and confirmed proposed methods for improving decision-making skills and effective education in classical martial arts [15]. Smart radio networks can use artificial intelligence technology for efficient sensing and decision-making.…”
Section: Introductionmentioning
confidence: 86%
“…Zhao uses bitter data processing and separation techniques to analyze the visual characteristics of a martial arts match. He evaluated abstract models and confirmed proposed methods for improving decision-making skills and effective education in classical martial arts [15]. Smart radio networks can use artificial intelligence technology for efficient sensing and decision-making.…”
Section: Introductionmentioning
confidence: 86%
“…The experiment begins after the preliminary preparations (Hildebrand et al, 2021 ; Zhang et al, 2021 ). The DNN used in the experiment is designed by Matlab toolkit, specified as follows.…”
Section: Research Model and Frameworkmentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Peer-review manipulation …”
mentioning
confidence: 99%
“…Tis article has been retracted by Hindawi following an investigation undertaken by the publisher [1]. Tis investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process:…”
mentioning
confidence: 99%